A qualitative study of mindfulness, sustainable consumption and consumer well-being and their interrelationships - Resnik, Saba (Economic and business review, 2022)
Consumers are becoming increasingly aware of the environmental degradation, negative economic consequences and social injustices caused by the unsustainable consumption of clothing products. Overall, therefore, sustainability requires more sustainable production of fashion apparel products as well as more responsible consumption behaviours by individual consumers. To gain a clearer picture of the concepts of mindfulness, sustainable consumption and consumer well-being and their interrelationships, in-depth interviews were conducted with individual consumers. The results of this study indicate a positive relationship between these three concepts as well as an overlap between the concepts of mindfulness and well-being.
Keywords: business strategy; consumerism; crowdfunding; čuječnost; mindfullnes; potrošništvo; start-up; sustainable development; trajnostni razvoj